1980
DOI: 10.1039/c39800000344
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterisation of a transient intermediate in rhodium-catalysed asymmetric homogeneous hydrogenation

Abstract: An unstable rhodium alkyl has been character-spectroscopy Thus (RR) -1,2-bis-(o-methoxyphenylised by n m r spectroscopy a t low temperatures under the phenylphosphino)ethane2 rhodium complexes of cx-benzconditions of homogeneous hydrogenation amidocinnamic acid (la) and its methyl ester (lb) exist as two diastereomers in ratio 10: 1 at room temperature These are co-ordinated to rhodium through olefinic and amide groups3 and differ in configuration of bound olefin At room temperature they disappear concomitantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 0 publications
6
56
0
1
Order By: Relevance
“…Consequently, the stereochemistry of the hydrogenation is regulated by this relative reactivity rather than by the relative thermodynamic stability of the diastereomers [73,75,77]. Halpern and Landis accomplished detailed kinetic measurements on the hydrogenation of methyl-(Z)-a-acetamidocinnamate [(Z)-MAC] enamide catalyzed by Rh(DIPAMP) species.…”
Section: Hydrogenation Of Iminesmentioning
confidence: 99%
“…Consequently, the stereochemistry of the hydrogenation is regulated by this relative reactivity rather than by the relative thermodynamic stability of the diastereomers [73,75,77]. Halpern and Landis accomplished detailed kinetic measurements on the hydrogenation of methyl-(Z)-a-acetamidocinnamate [(Z)-MAC] enamide catalyzed by Rh(DIPAMP) species.…”
Section: Hydrogenation Of Iminesmentioning
confidence: 99%
“…[76][77][78] A decrease in the reaction rate due to a stronger binding interaction between the sulfonate groups from the resin and the rhodium centres, after NBD has been reduced and replaced by weaker ligands in the first hydrogenation step, was hypothesised on these basis. However, the absence of any other resonance prevented an unambiguous explanation for the decreased catalytic activity.…”
Section: H T U N G T R E N N U N G (Tmbtp)a C H T U N G T R E N N U Nmentioning
confidence: 98%
“…Among them, the cationic Rh-diphosphane-enamide complex [7,10,14] and the alkyl monohydride species [8,12] have been characterised by various spectroscopic and X-ray-based methods. Also, the presumed dihydride intermediate has been investigated by PHIP (para-hydrogen induced polarisation) NMR spectroscopy, which is a powerful tool for studying hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical, [7][8][9][10][11][12][13][14] kinetic [9] and theoretical [15,16] studies have been carried out. As a result, the rhodium-catalysed hydrogenation of dehydroamino acids leading to enantiomerically pure α-amino acids is considered to be a thoroughly understood reaction based on work carried out in- the research groups of Halpern [7] and Brown [8] who revealed the underlying steps of the process. It has been demonstrated that the minor diastereomer resulting from the coordination of the enamide to the cationic Rh-diphosphane precursor reacts more rapidly with molecular hydrogen providing the observed prevailing hydrogenated product.…”
mentioning
confidence: 99%